The Wnt/β-catenin and PI3K/Akt signaling pathways promote EMT in gastric cancer by epigenetic regulation via H3 lysine 27 acetylation - Song, Yue; Li, Zhao-xia; Liu, Xi; Wang, Rui; Li, Li-wei; Zhang, Qingyu (Tumor biology, 2017)
In this study, we investigated the underlying mechanism of the phosphoinositide 3-kinase/Akt– and Wnt/β-catenin-mediated promotion of epithelial-to-mesenchymal transition by epigenetic regulation of histone acetylation in gastric cancer. First, we used immunohistochemistry to detect the expression of phosphorylated Akt, phosphorylated glycogen synthase kinase 3 beta, and β-catenin in gastric cancer tissues and adjacent tissues. In addition, we confirmed that the phosphoinositide 3-kinase/Akt and Wnt/β-catenin signaling pathways were correlated with tumorigenesis, progression, and maintenance of gastric cancer using the phosphoinositide 3-kinase inhibitor LY294002 and an inhibitor of the β-catenin/TCF4 complex, FH535. Epithelial-to-mesenchymal transition–related gene expression was measured by western blotting and quantitative real-time polymerase chain reaction assays. Furthermore, we detected the acetylation of histone H3 lysine 4 and lysine 27 using the FH535 and LY294002 inhibitors at different concentrations for 24 and 48 h. Finally, chromatin immunoprecipitation–quantitative polymerase chain reaction was performed to detect the specific binding of H3K27ac to the promoter of the epithelial-to-mesenchymal transition–related factor, Twist. Taken together, abnormal activation of the phosphoinositide 3-kinase/Akt and Wnt/β-catenin signaling pathway was correlated with the gastric cancer progression and contributed to epithelial-to-mesenchymal transition regulation by controlling histone acetylation.